Teachers’ Knowledge About Dental Trauma and its Management in Primary Schools in Jakarta, Indonesia - Yufitri Mayasari; Rahayu Dwi Setia Wibowo (Journal Research of Social Science, Economics, and Management, 2022)
Traumatic dental injuries often occur in children aged 7-12 years during school hours. However, most teachers are not aware of first aid for traumatic dental injuries. There are 2 types of elementary schools, namely public elementary schools and private elementary schools. This study aims to explain the difference in knowledge about traumatic dental injury and its first aid management  between public and private school teachers. Analytical research was conducted using a cross sectional approach and the sampling method was carried out using purposive sampling. Questionnaires in the form of Google Forms were used to collect data. Data were statistically analysed using Chi-square test for any correlation. Based on the results of the study that there is no significant difference in knowledge between public and private school teachers. The highest p-value is 0.752 and the lowest p-value is 0.102 (p > 0.05). So it can be concluded that this study did not find a significant difference in knowledge about first aid for traumatic dental injuries between public and private school teachers.